ANTAGONISM OF TRICHODERMA VIRIDE TO MACROPHOMINA PHASEOLINA AND ITS APPLICATION IN THE CONTROL OF DRY ROOT-ROT OF MUNG - SUDHlR CHANDRA, HARBANS KAUR KEHRI and (Indian Phytopathology, 2002)
The efficacy of u;1tagonist Trichoderma uiride in controlling the pathogenic activity of Macrophomina phoseolina, responsible for the dry root-rot of mung, was evaluated. The antagonist applied as seed coating reduced mortality due to M. phoseolina from 19 to 8 per cent in mung var TÂ·44 and from 19 to 10 per cent in var Pusa Baisakhi in unsterilized soil under greenhouse conditions. The biocontrol efficacy of the antagonist showed an improvement in sterilized soil. The dry weight of shoots, grains and nodules showed an increase of 31.7, 16.6 and 100.0 per cent respectively in TÂ·44 and 27.0, 32.1 and 133.3 per cent respectively in Pusa Baisakhi.